Development of the digestive organs in piglets born from sows consuming probiotic before farrowing and during lactation - Ayala, L?zara; Bocourt, Ram?n; Castro, Manuel; Dihigo, Luis Enrique; Mili?n, Grethel; Herrera, Magalys; Ly, Julio (Cuban Journal of Agricultural Science, 2014)
Morphometry characteristics of the digestive organs were determined in 24 piglets of 68 d of age and 21 kg of live weight, from a commercial cross and born from sows treated with Bacillus subtilis, before farrowing (0, 21 and 30 d) and during lactation (33 d). There was no effect of treatment on the relative fresh weight of the tract and digestive organs, although the small intestine showed low correlation (r = 0.237; P < 0.10), weighing less as the treatment days elapsed from 44.8 to 40.9 g/kg LW. The relative fresh weight of the small intestine was correlated with the gastrointestinal tract (r = 0.936, P < 0.001) and represented, as average, 59.1 % of the weight of the entire tract in this life stage of the animals. The linear density of the small intestine showed significant decrease (P < 0.05) when the treatment was extended in time from 0.60 to 0.53 g/cm. It is suggested that morphometry measurements of the alimentary canal could constitute an indicator of the response of piglets born from sows treated with Bacillus subtilis before farrowing and during lactation. Key words: piglets, Bacillus subtilis, probiotic, gastrointestinal tract, morphometry